Outros subsolos : uma análise de Uma criatura dócil - Vargas, Jéssica Souza (2016)
It is a fact that Dostoyevsky’s literary work is known worldwide not only when it comes to Russian literature; considering the visibility of his novels, most of them already translated directly from Russian. In order to think the “underground man” – his ultimate character – in all its aspects, we chose A Gentle Creature, a novella that shows a man who floats over the crowd and tries to understand it at the same time as he tries to understand himself. The proposal of the present study is to reveal this unreliable and delusional narrator who, in a desperate soliloquy, struggles to accept his wife’s suicide, the central action of the plot. The apparently always-in-development Saint Petersburg drives a philosophical question – the sinking inside of the human soul – and offers a social structure that pushes the conflict of an individual who tries to make himself present while he dialogues with the Other, who is also present. The alterity of the dead wife cannot be understood by the widower, in observations brought at the end of the analysis which, as a matter of fact, denies the singularity of the woman’s discourse, who cannot be understood as gentle or meak and who in her final act, death, finds a possibility of escape. Therefore, in order to think the Self and the Other, we used Emmanuel Levinas’ first philosophy. Taking this incomplete being as a result of the narrative, we studied aspects related to the subject’s unfinished speech by using concepts of authors such as Mikhail Bakhtin and Leonid Grossman, who also brought ideas about the structure of the novella genre, which was modified by Dostoyevsky. There were other authors selected to give basis to this study’s arguments and, moreover, to guarantee that the individuals (turned into presence through their words) could be a part of what we understand as reality, the same strange reality engendered by the author, who reveals to the reader two characters enclosed in their undergrounds, with no exit.